Cryptosporidiosis in the Isle of Thanet: an outbreak associated with local drinking water - Joseph, C. (1991)
An outbreak of cryptosporidiosis occurred in the Isle of Thanet during December 1990 and January 1991. A total of 47 cases ranging in age from 2 months to 85 years were identified in residents from the Margate, Broadstairs and Ramsgate areas, with dates of onset of illness from 3 December to 14 January. A case-control study demonstrated a strong statistical association between illness and the consumption of unboiled tap water from a particular source, with evidence of a dose—response relationship. Although no cryptosporidial oocysts were identified in samples of untreated or treated water taken during the investigation, the results were consistent with the view that the source of infection was treated river water which was used to supplement borehole water.